ANALISIS PENGARUH KUALITAS LAYANAN, HARGA, KEPERCAYAAN, CITRA PERUSAHAAN, DAN KEPUASAN PELANGGAN TERHADAP LOYALITAS PELANGGAN : (Studi Pada Pelanggan Telkom Speedy Di Palangka Raya) - Deddy Rakhmad Hidayat; Muhammad Riza Firdaus (JWM (JURNAL WAWASAN MANAJEMEN), 2014)
This study was made to determine and analyze the factors that affect customer loyalty, such as customer satisfaction, trust, corporate image shaped by service quality and price. Object of this study are household customers who subscribe SPEEDY more than 3 months in Palangka Raya. Techniques used in the sampling in this study was purposive sampling. With a sample of 110 people who qualify maximum likehood estimation of SEM. Data collection using questionnaires and the data were analyzed using Structural Equation Modeling (SEM) software with IBM SPSS Amos 20. Results and implications of this study is that theoretically this study supports previous research which states that service quality has positive and significant impact on corporate image, corporate image has positive and significant impact on customer satisfaction, customer satisfaction has positive and significant effect on confidence, and negatively affect prices significant impact on customer loyalty, customer satisfaction and a significant positive effect on customer loyalty